TANGGUNGJAWAB NOTARIS YANG TIDAK HADIR DALAM PEMBUATAN AKTA PERJANJIAN KREDIT DI BANK - Fitriani Iswandari, (The Juris, 2023)
Notaries are here to serve the interests of the public who need evidence in the form of authentic deeds. An increase in the number of deed legalized in 2018 from 64612 cases to 90037 cases in 2019. Every year the need for legalization services, especially the presence of a notary at the time of the credit agreement and the signing of the deed is very important, considering that the community's need for legal certainty is increasing. The research method used is normative juridical using secondary data, through an approach by examining theories, concepts, legal principles and laws and regulations related to research. The conclusion of this study is that the Notary is responsible for what is witnessed, namely what is seen, heard, and also done by the Notary. Guarantee that the deed made contains the truth/certainty, the correctness of the signature, the identity of the parties present, as well as the place where the deed was made, so that the notary has a great responsibility in fulfilling his obligations in serving the community, especially when the credit agreement is made at the bank with the deed made through his presence or substitute notary if the notary is unable to attend due to certain circumstances.